USING THE PROGRAM CONVERSION TEXT DOCUMENTS IN A COMPUTERIZED SYSTEM COMPARATIVE ANALYSIS OF ELECTRONIC TEXTS - Литвиненко, О.Є.; Лезвінський, О.С. (Science-based technologies, 2009)
In this Article were considred types and principles of code of text information. The system of Unicode is more in detail described and  also was indicated about word processors, Final part is development of simple converter of text documents from DOC in TXT format.